Weaving History: Archaeological Perspectives on Métis Lifeways in the 19th Century ... - Supernant, Kisha (University of Alberta Library, 2020)
SSHRC IG awarded 2021: Using five threads of a Métis worldview as represented by the Métis sash – geography and place, mobility, economy, daily life, and kinship relations (Macdougall, Podruchny, and St-Onge 2012), we propose research that weaves together archaeological, spatial, and historical data to provide insight into a Métis way of being in the nineteenth century. We apply this approach to two important landscapes in Alberta: the eastern side of Lesser Slave Lake in northern Alberta and the Bow/Elbow river drainages of southern Alberta. Our research team will use multiple methods drawn from different disciplines, including historical research, GIS and mapping, remote sensing, paleoethnobotany, paleomagnetic dating, and archaeological analysis, to illuminate Métis history connected to these specific places, as well as to the broader Métis homeland and living Métis families. ...